How Transformative Education Empowers Social Justice: Bridging the Gap between Knowledge and Action - Uthman, Yusuf Olawale OwaOnire (COMPETITIVE: Journal of Education, 2023)
This paper examines how transformative education can empower social justice by bridging the gap between knowledge and action. It presents a theoretical framework for transformative education, which is grounded in critical reflection, dialogue, and action. By fostering critical consciousness, transformative education enables students to challenge the systemic issues that perpetuate inequality and injustice. Drawing on examples from different educational contexts, this paper highlights the importance of adopting a transformative approach to education in order to create meaningful change in individuals and communities. Ultimately, it argues that transformative education can serve as a powerful tool for promoting equity, inclusion, and social justice in society. This study would base on a literature review of the existing research on transformative education and its relationship with social justice. The literature review draws on various academic databases, including research works, papers, articles, books, and reports published in several journals. The paper adopts a qualitative approach to analyze and synthesize the literature on transformative education and uses thematic analysis to identify key themes and concepts. The findings are presented in a narrative format and related illustration in the topic’s case study which is organized around the theoretical framework of transformative education. The paper also includes case studies and examples from different educational settings to illustrate the transformative potential of education in promoting social justice.